Peran Media dalam Perubahan Sosial Budaya Masyarakat - Erwan Efendi; Winda Kustiawan; Muhammad Fharisi; Ilham Sani (Peneliti.net, 2023)
Mass media is one of the factors that play an important role in social change of community culture. The role of mass media in social change of community culture is always related to diffusion of innovation. Change is driven by spread of new knowledge in society. Mass media has a role in the occurrence of social change in three aspects including (1) changes in people's mindset; (2) changes in community attitudes; and (3) cultural change. Mass media is a benchmark for the public to get information. By using literature studies, this paper aims to look at the role of mass media and contribute to all innovations that develop in society. The role of the mass media in education makes a change in the mindset and mentality of the nation. The role of mass media in the field of information dissemination can change people's attitudes. The role of the mass media in the entertainment community produces cultural material. In carrying out all of these roles, the mass media has a positive or negative impact according to the readiness of people to accept something new and the policy of the mass media owners to carry out their role in society